PENGARUH PROGRAM PENSIUN DAN PROGRAM KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP SEMANGAT KERJA KARYAWAN PT. BIRO KLASIFIKASI INDONESIA (PERSERO) CABANG BELAWAN - Harahap, Lokot Muda; Tampubolon, Andri R (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2017)
The conclusions from the study that there is a positive and significant effect of pension program and Occupational Health and Safety (K3) program on employee morale PT. Biro Klasifikasi Indonesia (Persero) Branch of Belawan. Obtained by multiple linear regression equation Y = 9.029 + 0.809 X1 + 0.197 X2 , which means that if the pension plan and occupational health and safety programs ernilai zero employee morale can be explained by 9.029 .The result showed that simultaneous variable pension program and Occupational Health and Safety (K3) program on employee morale PT. Biro Klasifikasi Indonesia (Persero) Branch of Belawan, where the value Fcount > F table or 24.197 > 3.23 with the level of significant (Î±) 0.000 < 0.005. While partial pension plan and a significant positive effect on employee morale with tcount = 6.298> t table = 2.021. Occupational Safety and Health Programs positive and significant impact on employee morale with tcount = 2.236> t table = 2.021.Coefficient of determination (R square) of 0.547 means the influence of retirement program and the Occupational Safety and Health Program (K3) on employee morale PT. Biro Klasifikasi Indonesia (Persero) Branch of Belawan by 54,7 % and the remaining 45,3% is influenced by other variables outside of research. Conclusions from the study that there is a positive and significant effect of pension program and Occupational Health and Safety (K3) program on employee morale PT. Biro Klasifikasi Indonesia (Persero) Branch of Belawan. Keywords : Pension Programs, Occupational Safety and Health Program, Morale